Rethinking human–nature relationships: Daoism's contribution to transcultural sociotechnical imaginaries - Miao-ling Hasenkamp; Zhanli Sun (The Professional Geographer, 2023)
Humans' imaginaries toward nature have profound implications for environmental governance and natural resource management strategies. Driven by relentless technological advancement, such imaginaries have undergone a series of transformations. Through a phenomenological and social constructivist perspective, this article aims to explore and explain the dynamics of transcultural sociotechnical imaginaries found in the connection between Western posthumanism's relational perspective on humans, nonhuman entities, and agency, on the one hand, and the emphasis on human–nature unity in the Chinese Daoist tradition, on the other hand. We argue that, by displacing an anthropocentric and Eurocentric frame, such transnational deliberation efforts grounded in a relational, geo-centered, and mediated frame offer planetary viewpoints to tackle the vast challenges currently faced by humanity. This discourse provides an alternative way of thinking to approach current environmental governance and natural resource management practices in the context of the increasing interconnectedness and cultural plurality of globalization. Hence, this article suggests exploring the potentials of the ideas of dwelling, landscapes, new ecologies, and mutual embeddedness suggested by Daoism and critical more-than-human geography at a local scale, which will pave the way for pragmatic pluralism and cultivate new attitudinal dispositions and capacity for systemic change. – – Los imaginarios humanos relacionados con la naturaleza tienen profundas implicaciones para la gobernanza ambiental y las estrategias de manejo de los recursos naturales. Impulsados por el incesante avance tecnológico, esos imaginarios han experimentado una serie de transformaciones. A través de una perspectiva constructivista fenomenológica y social, este artículo apunta a explorar y explicar la dinámica de los imaginarios transculturales y sociotécnicos hallados en la conexión entre la perspectiva relacional del poshumanismo sobre los humanos, las entidades no humanas y la agencia, por un lado, y el énfasis en la unidad hombre–naturaleza de la tradición chino-taoísta, por el otro. Argüimos que, desplazando una enmarcación antropocéntrica y eurocéntrica, tales esfuerzos de deliberación transnacional apoyados en un marco relacional, geocentrado y mediado, presenta punto de vista planetarios para tomar en consideración los grandes desafíos a los que actualmente se enfrenta la humanidad. Este discurso nos proporciona una manera de pensar alternativa para acercarnos a las prácticas actuales de gobernanza y manejo de los recursos naturales dentro del contexto de la creciente interconexión y pluralidad cultural de la globalización. Es por eso por lo que esta artículo sugiere explorar el potencial de las ideas de vivienda, paisajes, nuevas ecologías y mutua incrustación sugeridas por el taoísmo y la geografía crítica más-que-humana, a escala local, lo cual allanará el camino hacia el pluralismo pragmático y cultivará nuevas disposiciones de actitud y capacidad de cambio sistémico.
Keywords: 910; Daoism; environmental governance; human-nature relationship; postenlightenment; sociotechnical imaginaries; Taoísmo; gobernanza ambiental; imaginarios sociotécnicos; posilustración; relación hombre-naturaleza